The Witness Shop in Damascus and Cairo (from the middle of the seventh century to the first quarter of the tenth century AH) - Zaouari, Mohammed Abdullah (Journal of Humanities & Social Sciences, 2025)
In the early seventh century AH, new institutions appeared in the Levant and Egypt: Notarial Centers in the Levant and Notarial Shops or Booths in Egypt. They brought together contract scribes and witnesses whose signatures validated legal documents. While notaries and witnesses had existed since early Islam, they had worked separately, which complicated contract drafting and authentication. The creation of these offices unified their efforts and made the process easier for the public. Notarial shops soon became an informal extension of the judiciary, serving all social classes by drafting and authenticating contracts. Located near markets, schools, and courthouses, they engaged directly with society, offering legal advice, religious opinions, and forums for scholarly debate. They embodied the authority and dignity of the scholarly class while operating under judicial supervision. Despite their prestige, occasional misconduct drew criticism. Abolished after the Ottoman conquest, these institutions remain historically significant as evidence of an advanced stage in the evolution of the Arab judicial system, preceding similar developments in parts of the Western world.